How and Why to Regulate False Political Advertising in Australia - Hill, Lisa (Springer Nature, 2022)
This open access book represents the first comprehensive, Australia-focused treatment of the problem of false election information disseminated for the purpose of gaining an electoral advantage. It explores cautious legal regulation as the most effective and decisive approach to the issue. In doing so, the book demonstrates that, although experiments with such remedies have met with mixed success elsewhere, they are nevertheless viable, especially in Australia where they have strong public support and are able to withstand constitutional challenge.